2022
DOI: 10.1038/s42003-022-04268-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced excitatory neuron activity and interneuron-type-specific deficits in a mouse model of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is characterized by progressive memory loss and cognitive decline. These impairments correlate with early alterations in neuronal network activity in AD patients. Disruptions in the activity of individual neurons have been reported in mouse models of amyloidosis. However, the impact of amyloid pathology on the spontaneous activity of distinct neuronal types remains unexplored in vivo. Here we use in vivo calcium imaging with multiphoton microscopy to monitor and compare the activity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…This correlates well with observations of reduced mitochondrial function in AD mice at age 7-10 months (82) and reduced EEG rhythms observed in MCI patients (80). The lower DOE in our 8-9-month-old AD mice are likely a consequence of Aβ-induced impairments to mitochondrial function and diminished neuronal activity (82)(83)(84). Contrast-enhanced MRI measurements in APPswe/PS1dE9 mice showed no changes in relative cerebral blood volume (rCBV) at 8-month-old mice but significant reduction at 15-month-old mice (85).…”
Section: Discussionsupporting
confidence: 90%
“…This correlates well with observations of reduced mitochondrial function in AD mice at age 7-10 months (82) and reduced EEG rhythms observed in MCI patients (80). The lower DOE in our 8-9-month-old AD mice are likely a consequence of Aβ-induced impairments to mitochondrial function and diminished neuronal activity (82)(83)(84). Contrast-enhanced MRI measurements in APPswe/PS1dE9 mice showed no changes in relative cerebral blood volume (rCBV) at 8-month-old mice but significant reduction at 15-month-old mice (85).…”
Section: Discussionsupporting
confidence: 90%
“…Candidates for unclassified cells could be the relatively large population of oligodendrocyte precursor cells (about 5% of all cells in the brain (Dawson, Polito et al 2003)). After classifying the neurons into subtypes, 86% of all neurons were classified as excitatory and 14% as inhibitory (37199±1387 vs 6214±1001 respectively), which is in par with previous studies that reported 10-20% of neurons in layer 2/3 of the cortex being inhibitory interneurons (Kummer, Mitric et al 2020, Algamal, Russ et al 2022. In conclusion, cell type counts are comparable to published results, supporting the validity of our approach.…”
Section: Discussionsupporting
confidence: 88%
“…Mice used in this study, APP/PS1 hemizygotes on a C57BL/6;C3H-congenetic background (JAX Stock No. 004462), have alterations in excitatory/inhibitory (E/I) balance but no known report of IEDs has been documented (Algamal et al, 2021; Algamal et al, 2022; Yang & Jeong 2021). Mice were implanted with a two-shank linear silicon probe in the hippocampus spanning the CA1 layers and the upper blade of the dentate gyrus (Fig.…”
Section: Resultsmentioning
confidence: 99%